Practical guide to Information design - Lipton, Ronnie (Wiley, 2007)
Finally, in one usable format, here's your single-volume resource for designing clear projects that really work for your audience. The Practical Guide to Information Design provides all the tools, resources, and best practices that designers need to create highly successful print and digital information design projects.